2018
DOI: 10.1111/apa.14262
|View full text |Cite
|
Sign up to set email alerts
|

Using anaerobic blood cultures for infants younger than 90 days rarely showed anaerobic infections but increased yields of bacterial growth

Abstract: True anaerobic bacteraemia was extremely rare in neonates. Nevertheless, using anaerobic culture media may increase the overall yield of bacterial culture growth by isolating anaerobic-facultative bacteria. This should be weighed up against increasing the volume of blood used for the aerobic culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…The use of an anaerobic blood culture bottle is important not only for the recovery of anaerobic bacteria but also for the recovery of facultative anaerobes that grow better under anaerobic conditions. The use of an anaerobic culture bottle also reduces the time to detection of microbial growth [23,[30][31][32]. Our data confirm these findings.…”
Section: Discussionsupporting
confidence: 87%
“…The use of an anaerobic blood culture bottle is important not only for the recovery of anaerobic bacteria but also for the recovery of facultative anaerobes that grow better under anaerobic conditions. The use of an anaerobic culture bottle also reduces the time to detection of microbial growth [23,[30][31][32]. Our data confirm these findings.…”
Section: Discussionsupporting
confidence: 87%
“…[5] This is supported by studies showing that, despite the low prevalence of bacteremia by strict anaerobes in neonates and children (< 1%), as many as 11-22% of clinically relevant isolates were only detectable in anaerobic bottles. [19,20] This could be secondary to the anaerobic culture's more optimal conditions for growth of facultative anaerobic organisms that are prevalent in the neonatal population, like Streptococcus agalactiae. A study showed that there is additional value in the use of anaerobic bottles in very-low-birth-weight infants, where 16% of all cases of early-onset sepsis were secondary to obligate anaerobes.…”
Section: Discussionmentioning
confidence: 99%
“…A better use for the blood required to conduct the test would be to inoculate it into culture media. The criterion standard for late-onset sepsis is blood culture, and the accuracy of blood culture is driven directly by the volume of blood obtained for culture . The challenges of obtaining sufficient volume for culture in preterm infants have been well described .…”
mentioning
confidence: 99%